Revealed preference in a discrete consumption space - Matthew Polisson; John Quah (Institute for Fiscal Studies (IFS), 2012)
We show that an agent maximizing some utility function on a discrete (as opposed to continuous) consumption space will obey the generalized axiom of revealed preference (GARP) so long as the agent obeys cost efficiency. Cost efficiency will hold if there is some good, outside the set of goods being studied by the modeler, that can be consumed by the agent in continuous quantities. An application of Afriat's Theorem then guarantees that there is a strictly increasing utility function on the discrete consumption space that rationalizes price and demand observations in that space.
Keywords: 330; generalized axiom of revealed preference; Afriat's Theorem; discrete demand; utility maximization